Involuntary movements in an adolescent - Moreira,Mafalda (2024)
Abstract Extrapyramidal symptoms (EPS), such as dystonia, akathisia, and parkinsonism, are movement disorders that have been described as a side effect of antipsychotic medications in adults. In children, their use has expanded, as have this type of symptoms, especially those caused by first-generation antipsychotics. Paliperidone is a second-generation drug approved for schizophrenia in adolescents. The authors describe the case of a 12-year-old boy with a chronic disruptive behavior disorder who was admitted to the Emergency Department with tongue protrusion, inability to speak, eye rolling, and body tremors since that day. He was treated with paliperidone, the dose of which had been doubled in the previous month. Examination revealed dystonia of the eyes, mouth, and tongue, and increased neck tone. Biperiden was administered with complete resolution of symptoms after five minutes, and paliperidone was discontinued. This case suggests that caution should be exercised when prescribing antipsychotics (even second-generation agents). As the use of antipsychotics in children is increasing, pediatricians should be familiar with the acute presentation of side effects of these drugs.